Topiramate-induced severe heatstroke in an adult patient: a case report. (December 2016) - Canel, Lucie; Zisimopoulou, Sofia; Besson, Marie; Nendaz, Mathieu
Abstract Background Heatstroke is a life-threatening condition defined by failure of heat load dissipation, resulting in a core temperature higher than 40 °C (104 °F) associated with neurological dysfunction. Topiramate may cause anhidrosis, potentially resulting in heatstroke, as reported especially in children. Case presentation A 57-year-old Caucasian man was admitted to the emergency room in a febrile comatose state. After a complete workup ruling out the usual etiologies of such a condition, we assumed the hypothesis of a heatstroke caused by topiramate, recently prescribed for essential tremor. Conclusions Topiramate-related heatstroke has been described in children but must be recognized in adults as well. Outcomes may range from total clinical recovery to persistent neurological dysfunction or death. The prescription of topiramate and the follow-up of adult patients under this medication should include an evaluation of hypohidrosis, especially in contexts of high temperature.